Integrasi Literasi Kesehatan Digital dalam Perilaku Pencegahan Penyakit Tidak Menular pada Remaja Perkotaan Indonesia di Era Transformasi Layanan Kesehatan Nasional Berbasis Teknologi - Fahri Alfarizi; Dinaul Kamila; Fadlan Karim (Gema Cendekia Institute, 2025)
The transformation of technology-based national health services has changed the way adolescents access and utilize health information. This situation places digital health literacy as a critical competency in supporting non-communicable disease prevention behaviors from an early age. This study aims to analyze the integration of digital health literacy into non-communicable disease prevention behaviors among urban Indonesian adolescents. The study used a quantitative approach with a cross-sectional design, involving adolescents aged 15–18 years who reside in urban areas and have access to digital technology. Data were collected through an online questionnaire that measured digital health literacy and non-communicable disease prevention behaviors, then analyzed using descriptive and inferential analysis. The results showed that adolescents' digital health literacy levels were in the moderate to high category, with the greatest variation in the ability to critically evaluate digital health information. Digital health literacy was shown to be significantly associated with non-communicable disease prevention behaviors, particularly in aspects of physical activity and healthy eating. Adolescents with better digital health literacy tended to demonstrate more consistent preventive behaviors, even after accounting for sociodemographic factors. This study confirms that digital health literacy is a critical determinant in shaping adolescent health behaviors in the digital era. Integrating digital health literacy into health promotion programs and non-communicable disease prevention policies is expected to increase the effectiveness of technology-based health interventions and support sustainable adolescent health development.